2018
DOI: 10.3389/fpsyg.2018.00980
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Vitamin D3 Supplementation Affect Mood State 12 h Before 100 km Ultramarathon Run

Abstract: Background: Participation in extreme endurance sports is becoming an increasingly popular activity, and thus more and more people are getting involved in it. Taking part in a 100 km run is associated with great physiological and psychological stress, which can affect one’s mood state. Thus, the goal of this study was to determine if personality, experience, and motives for participation are related to a runner’s mood and its changes as well as to investigate whether vitamin D3 supplementation influences mood 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 58 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…In turn, experienced runners remember the pain and exhaustion of their previous runs, and often their fears are associated with unwillingness to experience these states again. Moreover, it is notable that the levels of tense arousal in the runners before the nighttime race were two stens higher than in runners who took part in our previous study, in which participants ran 100 km on a track [ 10 ]. It is not surprising that night ultramarathons are more of a mental challenge than a 100 km run on a flat, well-prepared track.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In turn, experienced runners remember the pain and exhaustion of their previous runs, and often their fears are associated with unwillingness to experience these states again. Moreover, it is notable that the levels of tense arousal in the runners before the nighttime race were two stens higher than in runners who took part in our previous study, in which participants ran 100 km on a track [ 10 ]. It is not surprising that night ultramarathons are more of a mental challenge than a 100 km run on a flat, well-prepared track.…”
Section: Discussionmentioning
confidence: 94%
“…Results of the research on the mood of ultramarathon runners are consistent [ 9 ]. The overwhelming majority of studies found, unsurprisingly, that after running an ultramarathon, levels of vigor drop, and levels of mental and physical fatigue increase [ 10 , 11 , 12 , 13 , 14 ]. Our research group observed similar results in our previous study conducted during a 100 km run on a track.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These scores can be combined by taking the sum of the negative mood states and subtracting the vigour score to produce a total mood disturbance (TMD) score [10]. The most consistently reported findings are pre to post race decrease in vigour and an increase in fatigue [10][11][12][13][14][15][16][17][18], which is consistent with fact that completing an ultramarathon requires sustained exertion.…”
Section: Introductionmentioning
confidence: 77%